The HER-2 as a Target Gene of Curcumin to Protect Hepatocytes Against the Arsenic-induced Carcinoma in Mice - Mahdi Ahadi; Vahid Naseh; Masoud Salehipour (Iranian Society of Pathology, 2017)
Background & objective: The HER-2 gene is an important on co protein overexpressed in many types of cancers. The current study hypothesized that curcumin downregulates HER-2 and inhibits the signal transduction pathway of PI3K/Akt, MAPK, and activation of NFκB, which could be useful to treat overexpressed-HER-2 hepatocellular carcinoma (HCC). Methods: In the current study, 40 male NMRI (Naval Medical Research Institute) mice were divided into 4 groups of 10 as follow: Group1 (control group) only received 5 mL/kg corn oil, group 2 (poisoned group) received 30 mg/L arsenic (As2O3) dissolved in water, group3 (curcumin treated), and group 4 (curcumin and arsenic treated) received 10 to 20mg/5mL/kg for 60 days. Once experimental period was completed, liver samples were collected. The analysis of the gene expression was performed by real-time polymerase chain reaction (PCR) technique. Results: Gene expression analysis showed that curcumin had significantly downregulated the activity of HER-2, in poisoned mice. Conclusion: According to the current study results, it could be concluded that curcumin has the inhibitory potential toward HER-2-overexpressed HCC.